Pengaruh Karakteristik Pemerintah Daerah Terhadap Kondisi Financial Distress Pemerintah Daerah Kabupaten dan Kota Se-Indonesia Periode 2015-2017 - Mutiara Sari; Fefri Indra Arza (Universitas Negeri Padang, 2019)
This study aims to obtain empirical evidence about the influence of the characteristics of local governments on local government financial distress in districts and cities throughout Indonesia for the period 2015-2017 whose data was obtained from the BPK and BPS. The dependent variable in this study is financial distress and its independent variables, namely the characteristics of local governments which consist of financial independence, the degree of decentralization, the complexity of local governments that are proxied by population, expansion of regions proxied by the administrative age of regional governments and area. The value of financial independence, population and regional expansion has a positive and significant effect on financial distress, while the value of the decentralization degree and area has a negative and significant effect on the financial distress of the regency and city governmen in Indonesia.Keywords: Local Government Finance, Characteristics of Local Government; Financial Distress